PREDIKSI TRAYEKTOR WAKTU-NYATA ROKET BALISTIK DENGAN MENGGUNAKAN GPS - Widada, Wahyu (Indonesian Journal of Aerospace, 2003)
This paper described the real-time prediction of the trajectory of a balistic rocket based on gps data. The method was used a parabolic motion under the assumption of a constant gravitational acceleration. The algorithm was successfully applied to GPS flight data of a RX150 rocket launched at Pameungpeuk, Jawa Barat